Characterization and Evaluation of Roselle and Kevlar Hybrid Composites Reinforced with Natural Fibers - Pradhan, Raghuram; Reddy, Yarram Srinivasa; Shariff, Md. Jabihulla (Theory and Applications of Engineering Research Vol. 7, 2024)
Over the previous three decades, materials with functionally graded and customized qualities have been produced. These components are extensively utilized in the system to save energy consumption and provide comfortable driving. Composite materials based on polymers are becoming more and more popular and are employed in a variety of fields. This book chapter centered essentially around the ongoing patterns and advancements in Bio compounds as connected to the therapeutic and building industry, referring to certain models. Present research is Alkali treated along with Silane treated and untreated fibres hybrid composite was prepared and all the types of physical and chemical properties studied. All the Silane treated composite shown enhanced concert than untreated composite. Performance possessions of composite devising various tenders in textile& non textile. Silane has an added advantage both physical and chemical properties enhancement.